Kemampuan Menulis Teks Deskripsi Siswa Kelas VII.6 SMP Negeri 1 Pagai Utara Selatan - Respelina Berisigep; Najmi Hayati; Yefrizon (JURNAL ARMADA PENDIDIKAN, 2023)
This study was motivated by the need to examine seventh-grade students’ ability to write descriptive texts at SMP Negeri 1 Pagai Utara Selatan. The research problem was formulated as follows: how is the descriptive-text writing ability of seventh-grade students at SMP Negeri 1 Pagai Utara Selatan? The study aimed to describe the descriptive-text writing ability of Grade VII.6 students at the school. A quantitative approach with a descriptive method was employed. The population consisted of 220 students from seven classes. The sample was selected using purposive sampling (non-random sampling design), with Grade VII.6 chosen as the sample class comprising 31 students. Data were collected through a performance test in the form of a descriptive-text writing task. Data analysis was conducted using descriptive quantitative procedures by calculating the mean scores for each indicator and the overall mean to determine mastery levels and performance qualifications. The results showed that Indicator 1 (object identification) achieved a mean score of 63.44 (fair), Indicator 2 a mean score of 76.34 (good), and Indicator 3 a mean score of 78.49 (good). The overall mean score was 74.55, which falls into the good category. The study recommends that instruction in descriptive-text writing place greater emphasis on structured practice in object identification through detailed observation, enrichment of descriptive vocabulary, and indicator-based feedback to improve students’ performance more evenly across all aspects.